Usaha – Usaha Perusahaan Dalam Meningkatkan Produktivitas Karyawan Melalui Latihan Kerja Dan Pengembangan Diri: Case Study at Navagreen Spa - Ari Nurcahyo Darmawan,; Ferra Eka Ramadhani,; Isabela Cikita Saputri, (JURNAL INOVASI SAINS TEKNOLOGI DAN BISNIS, 2022)
Increased staff productivity can give a business a competitive edge. The study's aim is to identify the impact of employee empowerment, job teamwork, and training on output. The study was carried out at Navagreen Spa. A total of 40 workers were chosen at random. A form was used to gather data, which was then scored using a Likert scale. The data is analyzed using Multiple Linear Regression. According to the results of this study, empowering factors, collaboration, and training all have a beneficial and substantial impact on employee output at Unagi Spa Bali. Empowerment is generally acknowledged as a critical factor in optimizing output. Carry out tasks The same team serves as the foundation for effective administration, with the goal of increasing total productivity outcomes. When employees obtain effective instruction, their productivity rises.